Risk factors of carcinoma cervix - Hachina Akhter; Ferdousi Begum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is a cancer of the cervix uteri. It may present with vaginal bleeding but symptoms may be absent until the cancer is in its advanced stage. Cervix is the commonest site for female genital cancer. Cancer cervix is the most common cancer in women in developing countries where screening facilities are inadequate. This study aimed to analyze the risk factors of carcinoma cervix. Methods: This descriptive study was conducted in Chittagong Medical College Hospital, taking 100 randomly selected patients of carcinoma cervix for one year (July 2019 to June 2020). The patients were selected from the gynae ward of Chittagong Medical College Hospital. Results: Among the study subjects, most of the respondents (32, 32.0%) belonged to 51-60 years old followed by (24, 24.0%) 41-50 years and >60 years of age. Maximum patients (84, 84.0%) were Muslim, followed by Hindu (14, 14.0). regarding occupation, a maximum (94, 94.0%) were housewives, and concerning marital status, most (88, 88.0%) of them were married. In this study, 36 (36.0%) patients had primary education followed by (30, 30.0%) secondary education. Most of the patients' spouses (32, 32.0%) were day laborers, followed by (24, 24.0%) service holders. In 78.0% of cases, the husband lived with the patients and 12.0% were apart but within the country and 10.0% live abroad. In 14.0% of cases, the husband had another sex partner. Among the study population, 18.0% of patients were habituated to chewing tobacco. Among the 100 patients multiparity (84.0%), early marriage (36.0%) early age of first intercourse (36.0%) and below average socioeconomic group (72.0%), and high-risk male partners (28.0%), and few multiple sex partner and STDs. Conclusions: In developing countries like Bangladesh, the majority of cases of carcinoma cervix are diagnosed at an advanced stage. Most of the cases were from poor to middle socio-economic backgrounds. Multiparity, early marriage, early age of first intercourse, and high-risk male partner were the main risk factors for the development of carcinoma cervix.